Implementation Of Registration Of Transfer Of Rights Reserved Land For Endowments By Permen Atr Bpn No. 2 Of 2017 In Pati Regency - Rubin Pratama; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this study was to identify and analyze: 1) Implementation of Registration of Transfer of Rights Reserved Land For Endowments By Permen ATR BPN No. 2 Of 2017 in Pati regency. 2) As a result of the Law of Registration of Transfer of Rights Reserved Land For Endowments By Permen ATR BPN No. 2 Of 2017 in Pati regency. 3) Barriers and Solutions in the Process of Registration of Transfer of Rights Reserved Land For Endowments By Permen ATR BPN No. 2 Of 2017 in Pati regency.The approach method in this research is juridical empirical research that emphasizes the behavior of individuals or communities in connection with the law. The data used are primary and secondary data obtained through interviews and literature, while the method of data analysis was done with descriptive qualitative analilis.Results of the research results can be concluded: 1) The registration of transfer of property rights to land as endowments by Permen ATR BPN No. 2 of 2017 in Pati regency categorized into two, namely for Waqf land registration activities that have not been certified (customary land) and the endowment of land that has been certified. For land that has not berserifikat documents furnished as the Deed of Pledge Waqf, copy of ID / KK, Ffoto copy of ID card / ID holder, a certificate of history of the land, a statement of physical mastery, the power of attorney request, a copy of property tax, proof of the right base / proof of ownership, a letter of disputes and probate Nadzir. As for the registration of land that has been certified requirements document completeness namely Deed Pledge endowment, land title certificates, copy of ID / KK Applicant, copy of ID / KK owner rights, petition, revelation of the grace period endowments, probate Nadzir, a statement of the land is not dispute, a statement of the land / building physically controlled, and evidence of CNS / PPH. 2) The legal consequences transitional registration of land titles for endowments, namely the status of Waqf land rights be have legal certainty. Waqf land registration set forth in Regulation ATR BPN Number 2 of 2017 concerning Procedures in the Ministry of Waqf Land Registration BPN ATR is a target to hold a legal simplicity. 3) Barriers still the majority community in Pati regency are still reluctant to take care certificate donated land, because of the assumption that the Waqf land certification process requires very expensive, the government's solution is to conduct information dissemination and outreach to the community.Keywords: Endowments; Land Registry; BPN